Emil Amberg papers - Amberg, Emil, 1868-
Correspondence, documents including bills and acts, clippings, printed matter, and scrapbooks relating to the pioneer work of the Wayne County Medical Society, Detroit, Mich., on interstate medical reciprocity and uniform medical legislation throughout the U.S.; the subsequent adoption of its proposal by the American Medical Association (AMA); medical education, ethics, law, and attitudes of the AMA on various medical and medicopolitical problems; Samuel Hahnemann; and other medical and scientific topics.
Physician.
Collection material in English.
Keywords: Hahnemann, Samuel, -- 1755-1843.; American Medical Association; Wayne County Medical Society (Wayne County, Ind.); Wayne-Union County Medical Society; Medical ethics; Medical laws and legislation; Medicine -- Practice -- Michigan -- United States; Medicine -- Study and teaching; Physicians